Problems of legal protection of selection achievements in the Republic of Kazakhstan (Journal of actual problems of jurisprudence, 2019)
This article displays the legal regulation of breeding achievements as оbjectof intellectual property, applieda new approach in the prism of three types of resources are displayed gaps and deficiencies of individuallegislative acts of the Republic of Kazakhstan, made suggestions to improve the legislation in the field ofagrarian business.Keywords: breeding achievements, intellectual property rights, agro-industry, agriculture, agriculturalbusiness.